ANALISIS PENERAPAN PSAK 109 TENTANG PELAPORAN KEUANGAN PADA LEMBAGA AMIL ZAKAT NURUL HAYAT CABANG MEDAN - Heriyati Chrisna (Jurnal Akuntansi Bisnis dan Publik, 2020)
Indonesian Institute of Accountants has issued acounting standards concerning financial statements charity, donation / charity. The standards contained in Statement of Financial Accounting Standards No. 109 (Revised 2011) regarding financial reporting zakat, infaq / sedeqah. This research was conducted at the Nurul Hayat LAZNAS Medan Branch which is one of the National Zakat Institution in the city of Medan. This study aims to know how the application of the recognition and measurement, presentation and disclosure of financial statements LAZNAS Nurul Hayat Medan Branch has been in accordance with SFAS 109 and to determine whether the application of the recognition and measurement, presentation and disclosure of financial statements LAZNAS Nurul Hayat Medan Branch has in accordance with SFAS 109. the analytical method used is descriptive qualitative to give a detailed picture of the background, characteristics and distinctive characteristics of the research subjects. The results showed that, Nurul Hayat LAZNAS financial statements were prepared using the Medan branch CYBER application diamana report zakat, infaq / sedeqah presented in the form of Fund Management Reports. Of the 15 provisions taken as a rule of SFAS 109, Nurul Hayat branch of Medan just follow the 5 conditions, or approximately 33.33% only in the application of SFAS 109 in preparing the financial statements. A total of 10 other provisions not in accordance with the provisions contained in SFAS 109. Therefore the application of SFAS 109 on LAZNAS Nurul Hayat Medan Branch has not been applied because of the limited power of human resources and lack of knowledge and training on accounting for zakat, donation / charity received by the employe.